2017
DOI: 10.1186/s12883-017-0813-6
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) inhibits proliferation and invasion of glioma cells by suppressing the Wnt/β-catenin signaling pathway

Abstract: BackgroundThe dysregulation of long noncoding RNAs (lncRNAs) has been identified in a variety of cancers. An increasing number of studies have found the critical role of lncRNAs in the regulation of cellular processes, such as proliferation, invasion and differentiation. Long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) is a novel lncRNA that was primarily detected in papillary thyroid carcinoma. However, the biological function and molecular mechanism of lncRNA PTCSC3 in gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 35 publications
(34 reference statements)
3
55
0
Order By: Relevance
“…In glioma, it is reported that CacyBP/SIP is upregulated and plays an important role in promoting cell proliferation (Shi et al, 2014). However, the migration and invasion behaviors of glioma are regulated by multiple signaling pathways Xia et al, 2017). However, we unexpectedly found that CacyBP/SIP exerted a role in inhibiting the glioma cell migration and invasion.…”
Section: Discussionmentioning
confidence: 72%
“…In glioma, it is reported that CacyBP/SIP is upregulated and plays an important role in promoting cell proliferation (Shi et al, 2014). However, the migration and invasion behaviors of glioma are regulated by multiple signaling pathways Xia et al, 2017). However, we unexpectedly found that CacyBP/SIP exerted a role in inhibiting the glioma cell migration and invasion.…”
Section: Discussionmentioning
confidence: 72%
“…lncRNAs have been reported to be involved in a variety of biological processes, including tumorigenesis through regulating oncogenes or tumor suppressors at several levels (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). For example, Xia et al (13) demonstrated that long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) inhibited proliferation and invasion of glioma cells by suppressing the Wnt/β-catenin signaling pathway. Su et al (14) illustrated that long noncoding RNA BLACAT1 indicated a poor prognosis of colorectal cancer and affected cell proliferation by epigenetically silencing p15.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with studies showing that the canonical Wnt/β-catenin pathway plays an important role in cellular migration and invasion in multiple tumor types including breast, prostate, gastric, hepatocellular, lung, and thyroid carcinoma cells. 4551 Pyrvinium has been shown to inhibit β-catenin driven gene transcription, but multiple different mechanisms can inhibit the Wnt/β-catenin pathway including interruption of Wnt interaction with the Frizzled/LRP receptor, 45,46,50 decreasing Wnt ligands, 49 abrogating β-catenin degradation, 51 or altering β-catenin’s interaction with transcription factors in the nucleus affecting gene transcription. 48 This suggests that drug targeting could be tested at a variety of different points in the Wnt/β-catenin signalling cascade making this a fruitful future direction in cancer therapy, including in WT.…”
Section: Discussionmentioning
confidence: 99%